1992
DOI: 10.1038/bjc.1992.183
|View full text |Cite
|
Sign up to set email alerts
|

Tumour proliferation assessed by combined histological and flow cytometric analysis: implications for therapy in squamous cell carcinoma in the head and neck

Abstract: Summary The two techniques of flow cytometry analysis (FCM) and immunohistochemical localisation of bromodeoxyuridine (BrdUrd) incorporation after in vivo administration, were combined to study proliferation in squamous cell carcinoma of the head and neck region. Care was taken in this study to ensure that similar material was processed using both techniques such that comparisons could be made. FCM underestimated the labelling index (LI) in tumours classified as diploid compared to the histological evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 16 publications
6
58
1
Order By: Relevance
“…The possibility of their use as a guide for selecting patients for accelerated treatment was subsequently tested. Since FCM tends to underestimate the proliferative activity of diploid tumours (Bennett et al, 1992;Høyer et al, 1998) it was combined with measurement of the LI using immunohistochemistry. Nevertheless, none of the proliferation parameters proved to be an independent predictor of treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of their use as a guide for selecting patients for accelerated treatment was subsequently tested. Since FCM tends to underestimate the proliferative activity of diploid tumours (Bennett et al, 1992;Høyer et al, 1998) it was combined with measurement of the LI using immunohistochemistry. Nevertheless, none of the proliferation parameters proved to be an independent predictor of treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…For immunohistochemistry 5 mm sections were mounted on poly-l-lysine coated slides. One section was stained with haematoxylin and eosin while other adjacent sections were immunohistochemically stained for IdUrd (Bennett et al, 1992;. For cell counting, high power fields (640 objective610 eyepiece) were captured and labelling was scored in a minimum of 1000 cells.…”
Section: Cell Proliferation Kinetics Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…LI can be evaluated either by FCM of cell suspensions or by morphometry in immunohistochemically (IHC) stained tissue sections. T can thus be calculated with LI derived either from histology or from FCM (Bennett et al, 1992). The findings by Dische and Saunders (1989), Rew et al (1991) and Wilson (1991) suggest that cell proliferation evaluated with this technique might be of independent prognostic value.…”
mentioning
confidence: 99%
“…1995). An extension of the technique has allowed identification of the cells preparing for division in histological material and has shown that in most squamous cancers there are areas where there is a potential for the number to double in less than 2 days (Bennett et al, 1992). High cell loss factors owing to maturation and degeneration largely account for the difference between the volume doubling times and potential cell doubling times of these tumours (Denekamp, 1982).…”
mentioning
confidence: 99%